Understanding The Poor Socio-Economic Investment Performance of Bihar: A Micro Perspective - Sah, Santosh (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
This paper investigates the underlying causes of poor economic growth of Bihar, India, despite being endowed with relatively rich natural resources. Against the conventional view, the analysis reveals that poor economic growth is not due to a particular factor but an outcome of a myriad of social, economic and political factors rooted in structural, historical and macro-economic policies. The economic marginalization of Bihar began in the colonial era through the establishment of an exploitative landlord class, which constantly resisted economic and social development even after independence in 1947. The process of marginalization has further been reinforced by the federal central government’s policy of ‘freight equalization’, which nullified the comparative advantage of Bihar in natural resources by subsidizing railway freights of industrial inputs like coal, iron ore, steel, cement and other bulk resources. This, combined with relatively low financial resources received from central government over the consecutive plan periods, has undermined these states’ capacity to invest in health, education, and other social and physical infrastructure and resulted in low human development. The poor performance of Bihar may be attributed to low human capital, weak institutions and poor infrastructure coupled with political instability and social conflict rooted in sectarian politics based on caste, class and ethnic division. Keywords:Economic Growth,Resources Endowment,Government Policy,Institutions, Bihar, India, Social